Environmental polycyclic aromatic hydrocarbons, benzo(a) pyrene (BaP) and BaP-quinones, enhance IgE-mediated histamine release and IL-4 production in human basophils - Kepley, Christopher L (Clinical immunology (Orlando, Fla.), 2003)
Polycyclic aromatic hydrocarbons (PAHs) are major components of diesel exhaust particles found in pollutant respirable particles. There is growing evidence that these fossil fuel combustion products exacerbate allergic inflammation. Basophils contribute to allergic inflammation through the release of preformed and granule-derived mediators. To determine whether allergens and PAHs interact, we incubated human basophils with PAHs and measured the release of histamine and IL-4 with and without added antigen. None of the PAHs induced mediator release by itself and none affected total cellular histamine levels. However, several PAHs enhanced histamine release and IL-4 production in response to crosslinking the high-affinity IgE receptor, Fc epsilon RI. The enhancement seen with 1,6-BaP-quinone involved an increase in tyrosine phosphorylation in several different substrates, including the Fc epsilon RI-associated tyrosine kinase, Lyn, and elevated reactive oxygen species (ROS) levels detected by dichlorofluorescein fluorescence and flow cytometry. The PAH-induced enhancement of mediator release and ROS production could be inhibited with the antioxidant N-acetylcysteine. These data provide further evidence that environmental pollutants can influence allergic inflammation through enhanced Fc epsilon RI-coupled mediator release from human basophils